2018
DOI: 10.1002/job.2278
|View full text |Cite
|
Sign up to set email alerts
|

Team learning from setbacks: A study in the context of start‐up teams

Abstract: Although setbacks often happen as a collective experience, teams are an underresearched organizational unit when it comes to learning from setbacks. Despite the popular view that experiencing setbacks may facilitate learning, there are conflicting theoretical assumptions about the influence of setbacks on learning. Whereas one theoretical perspective in this topic area is in line with the proverbial learning from failure, a competing perspective argues that setbacks impede learning processes. This study aims t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 116 publications
(269 reference statements)
2
25
0
1
Order By: Relevance
“…Shipp and colleagues have introduced the notion that an individual's temporal focus may change as a result of critical events and experiences. A supervisor who faces a traumatic work event (e.g., Yuan et al, ) or a team experiencing repeated performance setbacks (e.g., Rauter, Weiss, & Hoegl, ), for example, may subsequently alter their temporal focus. Examining such events in both field and laboratory settings may help to better comprehend the potentially dynamic nature of supervisor–team past temporal focus incongruence and its leadership consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Shipp and colleagues have introduced the notion that an individual's temporal focus may change as a result of critical events and experiences. A supervisor who faces a traumatic work event (e.g., Yuan et al, ) or a team experiencing repeated performance setbacks (e.g., Rauter, Weiss, & Hoegl, ), for example, may subsequently alter their temporal focus. Examining such events in both field and laboratory settings may help to better comprehend the potentially dynamic nature of supervisor–team past temporal focus incongruence and its leadership consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Here, Raykov (2004) highlighted the advantages of using SEM: "The approach provides both point and interval estimates of scale reliability, and in addition allows one to examine measurement DOI: 10.1002/piq Performance Improvement Quarterly and reliability invariance across independent or related groups" (p. 314). In other studies, Rauter, Weiss, and Hoegl (2018) identified the statistical technique while providing advantages of the techniques used. They utilized multiple-regression analysis with interactions.…”
Section: Examples Of Acceptable Methods Descriptions From the Literaturementioning
confidence: 99%
“…There is indeed an emotional impact of performance outcomes, and this impact is processed and stored differently when it is considered during a break and when there is no subsequent break, but rather continued effort without close interaction of team and coach. The gain in motivation for a team that has just received positive feedback through scoring a goal can indeed lead to improved performance and a win through a cognitive confirmation bias or through conservation of emotions [5][6][7][8]. This finding is important theoretically because there is yet little work on how such motivational effects linger under some circumstances and dissipate under other circumstances.…”
Section: Plos Onementioning
confidence: 99%